Improving The Ability Of Understanding Mathematical Concepts Through Mind Mapping Learning Model - Yusuf, Yusfita; Yuliawati, Lia; Juwita, Siti; Koswara, Ucu (UNIVERSITAS PAKUAN, 2023)
This research was motivated by the low ability of understanding mathematical concepts. One of the ways to improve the ability of understanding mathematical concepts was using Mind Mapping learning model. The purpose of this research was to determine the improvement of the ability of understanding mathematical concepts on cubes and blocks material using the Mind Mapping learning model. Furthermore, the Mind Mapping learning model was used to assess the attitudes of students toward mathematics learning. The method used in this research was quasi-experimental method. This research was conducted in two classes of VIII at SMPN 4 Situraja which functioned as an experimental class and a control class. The instruments used were tests of understanding mathematical concepts and student attitude questionnaires which given at the beginning and end of the lesson. The results of the analysis showed that the improvement of the ability of understanding mathematical concepts of students who used the Mind Mapping learning model was better than students who used conventional models